Control of grain size in rice by TGW3 phosphorylation of OsIAA10 through potentiation of OsIAA10-OsARF4-mediated auxin signaling - Ma, Ming; Shen, Shao-Yan; Bai, Chen; Wang, Wei-Qing; Feng, Xiao-Hui; Ying, Jie-Zheng; Song, Xian-Jun (Cell reports (Cambridge), 2023)
Grain size is a key component of grain yield and quality in crops. Several core players of auxin signaling have been revealed to modulate grain size; however, to date, few genetically defined pathways have been reported, and whether phosphorylation could boost degradation of Aux/IAA proteins is uncertain. Here, we show that TGW3 (also called OsGSK5) interacts with and phosphorylates OsIAA10. Phosphorylation of OsIAA10 facilitates its interaction with OsTIR1 and subsequent destabilization, but this modification hinders its interaction with OsARF4. Our genetic and molecular evidence identifies an OsTIR1-OsIAA10-OsARF4 axis as key for grain size control. In addition, physiological and molecular studies suggest that TGW3 mediates the brassinosteroid response, the effect of which can be relayed through the regulatory axis. Collectively, these findings define a auxin signaling pathway to regulate grain size, in which phosphorylation of OsIAA10 enhances its proteolysis and potentiates OsIAA10-OsARF4-mediated auxin signaling. [Display omitted] •TGW3 negatively regulates grain size in rice, which mediates brassinosteroid response•TGW3 interacts with and phosphorylates OsIAA10•OsIAA10 phosphorylation potentiates the OsIAA10-OsARF4-mediated auxin signaling•OsTIR1-OsIAA10-OsARF4 defines a genetic pathway for controlling rice grain size Grain size is a key component of grain quality and crop yield. Ma et al. show that TGW3 interacts with and phosphorylates OsIAA10, which favors OsIAA10’s interaction with OsTIR1 and destabilization but hinders its interaction with OsARF4. The genetically defined OsTIR1-OsIAA10-OsARF4 axis is required for grain size control in rice.